Multi-dimensional role of AGEs in periodontitis: from matrix remodeling to neuro-immune crosstalk - Dong, Yu-Lei; Lin, Hai; Wen, Tao; Guo, Zhu-Ling (Frontiers in Immunology, 2025)
Advanced Glycation End Products (AGEs) are key pathogenic drivers in periodontitis, a chronic inflammatory disease leading to destruction of tooth-supporting tissues. This review synthesizes evidence on the multi-dimensional roles of AGEs, focusing on three core areas: direct modification and degradation of the periodontal extracellular matrix (ECM), induction of a self-perpetuating inflammatory cycle via the Receptor for AGEs (RAGE), and dysregulation of the local neuro-immune axis, an emerging pathogenic frontier. AGEs, which accumulate with age and in metabolic diseases like diabetes, trigger pro-inflammatory signaling (e.g., NF-κB, MAPKs), leading to oxidative stress, cytokine release, and matrix metalloproteinase (MMP) activation. This disrupts ECM homeostasis by suppressing collagen synthesis while promoting its degradation. Notably, specific AGEs like Nϵ-(carboxymethyl)lysine (CML) directly induce osteoblast apoptosis, contributing to alveolar bone loss. A crucial, and increasingly recognized, aspect of AGE pathology is their ability to modulate neuro-immune crosstalk by activating both immune cells and sensory neurons. This creates a complex inflammatory network that exacerbates tissue damage and may contribute to clinical manifestations such as pain and chronic disease. The interplay between systemic AGE load and local production within inflamed periodontal tissues establishes a vicious cycle, making periodontitis a compelling model for studying AGE-driven pathology. Understanding this integrated network reveals novel therapeutic targets aimed at inhibiting AGE formation, blocking RAGE signaling, and modulating downstream inflammatory and neuro-immune pathways to improve periodontal and potentially systemic health.